Effect of air voids content on thermal properties of asphalt mixtures - Hassn, Abdushafi; Aboufoul, M.; Wu, Y.; Dawson, Andrew; Garcia, Alvaro (Elsevier, 2016)
Air voids content is considered as one of the factors that may affect heat transfer through asphalt mixture, although their specific role on the asphalt mixture temperature is still unclear. The objective of this research is to have a deep insight of the effect of air voids content on the temperature evolution, transport and storage of heat in asphalt mixture under dry conditions. With this objective, asphalt mixture slabs with different air voids content have been built and their thermal conductivity, specific heat capacity, light absorptivity and thermal diffusivity related to their temperature evolution have been measured when they are exposed to infrared light and during the cooling process. It was observed that asphalt mixture with high air voids content exhibited slightly higher steady state temperatures than denser asphalt mixture and that the heating and cooling rates are higher in porous asphalt mixture than in denser materials. The reason for the faster increase and decrease in temperature of porous mixture and for the higher temperature reached by porous asphalt is its lower specific heat capacity and thermal conductivity. Finally, it could be observed that the connectivity of air voids in asphalt mixture did not play an important role on the temperature reached by asphalt mixture.